HUBUNGAN ANTARA HYGIENE GIGI DENGAN KEJADIAN PNEUMONIA PADA BALITA UMUR 36-59 BULAN DI PUSKESMAS KLIRONG II - Septiwi, Cahyu; -, Basirun; Utmah, Eli Solihatun (LPPM STIKES MUHAMMADIYAH GOMBONG, 2009)
The pneumonia is health problem in world because the death level pneumonia desease hight, not only in proceed country but also in modern countries such as Amerca Serikat, Canada dan Eropa country. Some factors of risk pneumonia for example age, weather or climate, bad toht hygiene act. The purpose of this research is to know sum of children under five years old that suffering pneumonia, to know the sum of child pneumonia that bad tooht hygiene. Case Control with the approach of Retrospektive sampling. Populatian of the child 36-59 moth that suffering pneumonia in manistran Center the society Healt of Klirong II of 32 person . Analys the date with the analisys of is non parametrical statistic that is Spearman rho correlatian analys. Instrumen used check list observ of condition tooht hygiene on child under five years old. Sum of pneumonia child that bad tooht hygiene are 17 person. The result of date analys using Spearman rho test with statistic technique is P value 0,024, show that there are correlation betwen bad tooth hygiene and occurance pneumonia in children under five tears old. Information about pneumonia is needed to mother child that suffering pneumonia to decrease occurance pneumonia in child under five years old. Keywords: Bad tooht hygiene, Occurance pneumonia, The child under five years old.